Finite element analysis of the influence of anterior talofibular ligament injury on Hook test results. Issue 7 (July 2017) - Zhou, Lin; Lin, Yongxin; Zhai, Xu; Wang, Bata; Lin, Jiaming
Abstract: Aim: To determine whether the anterior talofibular ligament injury will influence the Hook test result. Method: A three-dimensional model of the ankle was established based on CT scan of a healthy volunteer and ligament attachment through references; Four groups (A–D) of operating conditions were set up. In group A, the anterior and posterior ligaments of the inferior tibiofibular joint were cut off and the anterior talofibular ligament was kept intact; in group B, all the anterior and posterior tibiofibular ligaments and the anterior talofibular ligament were cut off; in group C, the medial and lateral ligaments of the ankle joint and the inferior tibiofibular ligament were kept intact; in group D, only the talofibular ligament was cut off and other ligaments were kept intact. The proximal end of the model was restrained in all four groups, an outward pulling force of 100 N perpendicular to the fibula was applied, and displacement and rotation of the distal end of the fibula in the four groups was observed. Results: When the inferior tibiofibular joint injury was associated with an anterior talofibular ligament injury, the Hook test indicated about 3.19 mm of displacement of the distal end of the fibula, and obvious external rotation occurred due to increased activity of the anterior border of the fibula. In the other groups, a single inferior tibiofibular joint injury or a single anterior talofibular ligament injury did not increase displacement or rotation of the distal end of the fibula.